Clinical variables associated with late-onset thrombotic and cardiovascular events, after SARS-CoV-2 infection, in a cohort of patients from the first epidemic wave: an 18-month analysis on the “Surviving-COVID” cohort from Bergamo, Italy - Benatti, S. V.; Venturelli, S.; Crotti, G.; Ghirardi, A.; Binda, F.; Savardi, M.; Previtali, G.; Seghezzi, M.; Marozzi, R.; Corsi, A.; Bonaffini, P. A.; Gori, M.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Population studies have recorded an increased, unexplained risk of post-acute cardiovascular and thrombotic events, up to one year after acute SARS-CoV-2 infection.To search for clinical variables and biomarkers associated with late post-acute thrombotic and cardiovascular events after SARS-CoV-2 infection.Retrospective cohort study.Third-level referral hospital, in Bergamo (Italy).Analysis of an existing data-base of adult patients, cared for SARS-CoV-2 infection at our institution between 20 th February and 30 th September 2020, followed-up on a single date ("entry-date") at 3-6 months.Initial infection by SARS-CoV-2.Primary outcome: occurrence, in the 18 months after entry-date, of a composite endpoint, defined by ICD-9 codes for at least one among: cerebral/cardiac ischemia, venous/arterial thrombosis (any site), pulmonary embolism, cardiac arrhythmia, heart failure.Measures (as recorded on entry date): history of initial infection, symptoms, current medications, pulmonary function test, blood tests results, semi-quantitative radiographic lung damage (BRIXIA score). Individual clinical data were matched to hospitalizations, voluntary vaccination against SARS-CoV-2 (according to regulations and products availability), and documented reinfections in the following 18 months, as recorded in the provincial Health-Authority database.A multivariable Cox proportional hazard model (including vaccine doses as a time-dependent variable) was fitted, adjusting for potential confounders. We report associations as Hazard Ratios (HR) and 95% Confidence Intervals (CI).Among 1515 patients (948 males, 62.6%, median age 59; IQR 50-69), we identified 84 endpoint events, occurring to 75 patients (5%): 30 arterial thromboses, 11 venous thromboses, 28 arrhythmic and 24 heart-failure events. From a multivariable Cox model, we found the following significant associations with the outcome: previous occurrence of any outcome event, in the 18 months before infection (HR 2.38; 95% CI 1.23-4.62); BRIXIA score ≥ 3 (HR 2.43; 95% CI 1.30-4.55); Neutrophils/Lymphocytes ratio ≥ 3.3 (HR 2.60; 95% CI 1.43-4.72), and estimated-glomerularfiltration-rate < 45 mL/min/1.73m 2 (HR 3.84; 95% CI 1.49-9.91).We identified four clinical variables, associated to the occurrence of post-acute thrombotic and cardiovascular events, after SARS-CoV-2 infection. Further research is needed, to confirm these results.